A construção da identidade docente : uma reflexão sobre minhas experiências de estudante de pedagogia - Santos, Edicléia Cardoso Santana (2019)
This monograph aims to present the main brands of the course of pedagogy for the Constitution of a future teacher identity. Bring ideas from Freire (2014), Tardif (2013), Franco (2008; 2012), Vampire (2009) as base, as well as other authors that also contribute to my reflection, growth, and learning about the challenge that appears as an important way to understand the intertwined between the teacher and the educational practice identity, to assist and answer the demands required of a students, from the reality experienced try lifting strategies that allow the training to be a teacher, during the course, which lasts four years ago, in which the experiences come to broaden the concept of the formation of a professional aware of your role, understanding the real meaning and the importance of education. Therefore, this research clarifies how the student reaches the Pedagogy course with an image built what is teaching and this image will be built and rebuilt over the course of the training, in the period of four years, and, with this process, he will by creating your identity. In this sense, comes the answer: as the students built the identity of what it means to be a teacher at the end of the course of pedagogy? The methodology's bibliographic character, articulated to the memorial, which recounts the history of the construction of my teaching identity during passage through the course. The reflection on the rite of passage as a student of the course of pedagogy has led me to conclude that the development of the teaching practice of social quality is required a solid theoretical and methodological training in order to provide pedagogical situations for the student to be open and able to produce new knowledge. In this sense, the formation, on Pedagogy, especially the construction of the course work, contributes significantly to sharpen the epistemological curiosity, stimulating the search for answers, developing student's creative ability and teasing fundamental changes in the same. Curiosity as concern leads to questions which allow the unveiling of something unknown, still providing the evolution of naivety to criticality. That's what I can tell from my teaching identity construction.